An independent examination of the mindful sport performance enhancement protocol in National Collegiate Athletic Association Swimming and Diving - Kostrna, J.; D`Addario, A. (Journal of Clinical Sport Psychology, 2023)
The mindful sport performance enhancement (MSPE) protocol is designed to enhance mindfulness, emotional regulation, and attentional awareness and control. The MSPE consists of trainer led group sessions teaching the concepts of mindfulness through discussion and meditation practice. However, little research has tested the MSPE protocol`s adaptability and generalizability to National Collegiate Athletic Association (NCAA) Division-I teams and practitioners independent of the MSPE protocol`s creators. Therefore, the aim of the present study was to test the efficacy of an adapted MSPE protocol. The adapted MSPE protocol was delivered to a NCAA Division I team while a second team participated as a potentially equivalent control group. Both teams completed measures of attentional control, flow, rumination, and mindful attention as primary outcome variables. Results revealed significant decreases in rumination and trait anxiety, as well as improvements in concentration control and focusing ability compared with the control group. Findings support the external validity of the MSPE protocol to adapt to independent practitioners and a previously unstudied combination of sport and level of competition.